Major recommendation based on PMR result - Munirah, Ab Rahman (2010)
Upon obtaining their PMR's result, most students will meet their school's coordinator level or counsellor to discuss the suitable majoring based on their examination result. Through this 4ystem, student only need to include their examination results and this system will issue suitable major decision with their qualification. Apart from that, students can obtain complete information for majoring offered for form four. The objective of this system is to select majoring for students based on PMR results. The students have to enter their PMR results and this system will recommend the best major for them. This system is developed by using Hypertext Preprocessor language (PHP) and MySQL as their design database. This system is designed for Sekolah Menengah Kebangsaan Bukit Baru and has been tested by the school counsellor.